L'effet du renforcement de l'hydroxyapatite d'origine biologique sur les propriétés physico-chimique d'un composite dentaire - دودي مروه – باسي ايناس (university of eloued جامعة الوادي, 2024)
منذ أكثر من 60 عاماً، استمر طب الأسنان في التقدم من خلال تطوير أو استبدال الطرق والمواد التقليدية لترميم الأسنان بأخرى وظيفية وجمالية وأكثر أماناً على صحة الإنسان، ولا سيما من خلال استبدال الأملغم بالراتنج، لأن الأملغم يحتوي على مواد سامة. يحتوي الراتينج المحضر في المختبر على مرحلة عضوية مكونة من Bis-GMA كمونومر، وTEGMA كمخفف، وCQ كمحفز ضوئي، و DMAEMA كبادئ، ZrO2 وHA كمرحلة غير عضوية HA) مأخوذ من عظام الأبقار كمصدر طبيعي له. (ان نسبة المونمرات، ونوع وحجم الحشو هي عناصر يمكن ان تؤثر على خصائص المركب، لمعرفة ذلك تم تحضير عينات مختلفة النوع ومتفاوتة النسب. تم استخدام التحليل الطيفي FTIR لهذه العينات قبل وبعد البلمرة لتحديد نوع الحشو والنسب الأمثل لكل من الطور العضوي وغير العضوي لتشكيل المركب السني. Dentistry has been advancing significantly over the past 60 years by developing or replacing traditional methods and materials to repair teeth with functional, aesthetic, and safer ones for human health. This has been particularly achieved by replacing amalgam with resin, as amalgam contains toxic materials. The resin prepared in the laboratory consists of a monomer Bis-GMA, a diluent TEGDMA, a photamorceur CQ, DMAEMA as initiateur, ZrO2 additive, and HA as inorganic phase (HA derived from cow bones as a natural source). The ratio, type, and size of the filler are factors that can affect the compound's properties. To determine this, different types of samples with varying ratios were prepared. The FTIR analysis was used for these samples before and after polymerization to identify the type of filler and the optimal ratio for both organic and non-organic phases to form the dental compound
مدكرة ماستر كيمياء
Keywords: مركب الاسنان، هيدروكسي-اباتيت، بلمرة ضوئية، مطيافية الاشعة تحت الحمراء، عظام البقر.; Dental composite; Hydroxyapatite; Photo-polymerization; Infrared spectroscopy; Bovine bones